Breast cancer care system - Chin, Beatrice (University Malaysia Sarawak, (UNIMAS), 2006)
The emergence of the Internet has impacted the health information and the healthcare industry. The information revolution has reduced the distance between the healthcare provides and consumers. It permits easy dissemination of information and fast accessibility of data. With the rising cases of breast cancer among women in our country, an idea to develop a web-based system to manage breast cancer patient's health record evolves. The development of this system is expected to not only altered the way that medical information is stored, shared, and generated across and within healthcare organizations but it also promises to increase the efficiency and cost-effectiveness of healthcare, specifically in the realm of breast cancer.